Durable response of primary cardiac lymphoma after autologous stem cell transplantation and sequential CAR-T therapy: a case report and literature review - Wang, Ge; Zhou, Xiaoxi; Wang, Pengcheng; Mao, Zekai (Frontiers in Immunology, 2025)
Primary cardiac lymphoma (PCL), an exceedingly rare and aggressive extranodal lymphoma confined to the heart and/or pericardium, poses significant diagnostic and therapeutic challenges with a historically dismal prognosis. We present the first documented case of PCL achieving sustained complete response (CR) through a novel therapeutic approach combining autologous hematopoietic stem cell transplantation (ASCT) with sequential tandem CD19/20 CAR-T therapy. A 55-year-old female presented with chest tightness and pericardial effusion in April 2023. The diagnostic process involved multiple modalities and analyses, culminating in a diagnosis via CT-guided mediastinal lymph node biopsy. The patient underwent several chemotherapy regimens, including combinations of rituximab and polatuzumab vedotin, R-CHOP, Pola-R-CHP, and Pola-R-DA-EPOCH, which led to symptom relief and partial response. Subsequently, ASCT was performed, followed by sequential tandem CD19/20 CAR-T therapy. As a maintenance treatment, the PD-1 inhibitor sintilimab was administered approximately every two months. The patient achieved CR at month 3 and maintained CR for one year following the CAR-T infusion. Following CAR-T therapy, the patient developed immune effector cell-associated hematologic toxicity, which was managed with granulocyte colony-stimulating factor injection and supportive care. This case illustrates the difficulties in diagnosing and treating PCL. Through the combination of ASCT and sequential tandem CD19/20 CAR-T therapy, the patient achieved sustained CR with manageable toxicity. This case demonstrates the feasibility, safety, and potential efficacy of this combination strategy in treating high-risk lymphoma. Moreover, we propose a structured algorithm that may help optimize the clinical implementation of CAR-T therapy in similar cases. Continued follow-up and broader studies are warranted to validate these findings.